Substantial rise in the lifetime risk of primary total knee replacement surgery for osteoarthritis from 2003 to 2013: an international, population-level analysis. Issue 4 (April 2017) - Ackerman, I.N.; Bohensky, M.A.; de Steiger, R.; Brand, C.A.; Eskelinen, A.; Fenstad, A.M.; Furnes, O.; Garellick, G.; Graves, S.E.; Haapakoski, J.; Havelin, L.I.; Mäkelä, K.; et al.
Summary: Objective: To estimate and compare the lifetime risk of total knee replacement surgery (TKR) for osteoarthritis (OA) between countries, and over time. Method: Data on primary TKR procedures performed for OA in 2003 and 2013 were extracted from national arthroplasty registries in Australia, Denmark, Finland, Norway and Sweden. Life tables and population data were also obtained for each country. Lifetime risk of TKR was calculated for 2003 and 2013 using registry, life table and population data. Results: Marked international variation in lifetime risk of TKR was evident, with females consistently demonstrating the greatest risk. In 2013, Finland had the highest lifetime risk for females (22.8%, 95%CI 22.5–23.1%) and Australia had the highest risk for males (15.4%, 95%CI 15.1–15.6%). Norway had the lowest lifetime risk for females (9.7%, 95%CI 9.5–9.9%) and males (5.8%, 95%CI 5.6–5.9%) in 2013. All countries showed a significant rise in lifetime risk of TKR for both sexes over the 10-year study period, with the largest increases observed in Australia (females: from 13.6% to 21.1%; males: from 9.8% to 15.4%). Conclusions: Using population-based data, this study identified significant increases in the lifetime risk of TKR in all five countries from 2003 to 2013. Lifetime risk of TKR was as high as 1 in 5 women in Finland, and 1 in 7 males in Australia. These risk estimates quantify the healthcare resource burden of knee OA at the population level, providing an important resource for public health policy development and healthcare planning.